Private security and the investigative process - Nemeth, Charles P. (Butterworth-Heinemann, 2000)
Practical yet authoritative, Private Security and the Investigative Process, Second Edition, is an important reference tool for private investigators and security professionals. Both students and seasoned security practitioners alike will benefit from the resources, ideas, and suggestions for tactics and security strategy contained within this book. Charles P. Nemeth expertly blends practice with theory to show students how to be professional when confronted with the rigors of the real world, in both the public and private sectors. Private Security and the Investigative Process, is ideally suited for private security organizations, criminal justice libraries, corporate security personnel, and law enforcement personnel.